Design of high force density fishbone-shaped electrostatic actuator using finite element / Megat Muhammad Ikhsan Megat Hasnan - Megat Muhammad Ikhsan , Megat Hasnan (2014)
This study presents the design and evaluation of high force density fishbone shaped electrostatic comb drive actuator. The fishbone shaped comb drive actuator has structure similar to fishbone, which is intended to increase the capacitance of the electrodes, and hence increase the electrostatic actuation force. Two-dimensional finite element analysis was used to simulate the motion of the fishbone shaped electrostatic comb drive actuator, and compared against the performance of a straight sided electrostatic comb drive actuator. The performances of both designs are compared by evaluating the displacement and electrostatic force for both systems. For both cases, the active area and the minimum gap distance between the two electrodes were kept constant. Performance comparison of the fishbone shaped electrostatic comb driver and straight finger electrostatic comb driver are demonstrated with an active area of 800x300 μm2, which contained 16 fingers of fishbone shaped actuators and 40 fingers of straight sided actuators, respectively. Through the modeling and simulation, improvement of drive force of the fishbone shaped electrostatic comb driver is approximately 485% compared to the straight comb finger of conventional electrostatic comb driver. These results indicate that the fishbone actuator design provides good potential for applications as high force density electrostatic micro actuator in MEMS systems. The fishbone shaped comb driver introduced in this work shows a characteristic stepped force profile versus finger engagement compared to the conventional straight sided comb driver. However, a cogging effect was demonstrated, due to the negative force components of the fishbone shaped comb driver. So, a finger shifting method in comb arrays was introduced to mitigate the negative force profile, in order to ensure more linear electrostatic force profile.